A Study to Analyze the Trust of the Indian Youth on the Credibility of the Media - Shukla, Seema; Rai, Sushil (Journal of Advanced Research in Journalism & Mass Communication, 2019)
The Media is considered as the Fourth Pillar’ of a democratic society. It works as a watchdog over the legislative, executive and judicial systems of the government. The media’s fair and unbiased reporting is essential for the smooth and better functioning of a democratic setup. It has been observed that the Indian media is involved in several ill practices in order to generate revenue which has impacted its credibility. Today, most of the media is not able to maintain the core objectives of journalism; by presenting unverified fake news and delivering half- truths or fabricated news to generate a high TRP. It is essential to study the role of Indian mainstream media in disseminating fake news and the perception of youth towards the declining credibility of the Indian media today. Hence, this study looked into the participation of Indian mainstream media in spreading fake news as well as the approach of the Indian youth towards the declining credibility of the Indian media and how they are contending with credibility issues? How to cite this article: Shukla S, Rai S. A Study to Analyze the Trust of the Indian Youth on the Credibility of the Media. J Adv Res Jrnl Mass Comm 2019; 6(2): 1-5.